Feasibility study on preparing economical and environmentally-friendly high-flowability ultra-high performance cementitious composites with original graded stone powder free recycled manufactured sands. (1st March 2023) - Ma, Rui; Zhang, Lifeng; Song, Yufeng; Lin, Gaohang; Qian, Xiaoqian; Qian, Kuangliang; Ruan, Shaoqin
Abstract: With the depletion of river sand and the rising price of quartz sand, more and more researchers are trying to use manufactured sand to prepare ultra-high performance concrete (UHPC). However, due to the large amount of fine particles and high water demand, few studies are available to directly use the manufactured sand in its original state to prepare UHPC. To overcome the above problems, in this study, two locally available recycled manufactured sands are used as aggregates, and an attempt is made to maximize the use of their original gradation to prepare a cleaner construction production integrating high flowability, excellent mechanical performance, high cost-effective and environmentally-friendly property that meets the engineering requirements. The properties of workability, mechanical strengths, volume stability, hydration degree, pore structures, morphology of interfacial transition zone (ITZ), carbon emission and production cost are evaluated and discussed. Results indicate that all the mixtures prepared in this study can be considered to have high flowability except when granite sand is completely used. The mixture containing 75% tuff sand can even reach a compressive strength of 166.2 MPa, which is 10.5% higher than the reference one. A reduction of 28.9% can be observed in the early-age autogenous shrinkage of tuff sand UHPC as compared to the reference specimen. The mercury intrusion porosimetry (MIP) and X-ray computed tomography (X-CT) results demonstrate that the micropore volume, porosity and number of mesopores of UHPC increase to a certain extent when manufactured sand is utilized. The scanning electron microscope (SEM) observation reveals the most compact ITZ between cement paste and waste tuff sand. Additionally, the recycled manufactured sand UHPC can diminish the carbon emission of 19 kg and the cost of 27.4% (granite sand) and 25.5% (tuff sand) per cubic meter, showing excellent environmental and economical benefits. Highlights: Two locally available recycled manufactured sands were used to replace the refined quartz sand. An attempt was made to maximize the use of the original gradation of the recycled sands. The CO2 emission was diminished by 19 kg and the prices were lowered by at least 25.5% to produce 1 m 3 manufactured sands UHPC. The prepared cleaner production integrated high flowability, advanced mechanical properties and excellent environmental and economical benefits.